具有人源化淋巴细胞活化基因3的非人动物 (2021)
本发明提供了非人动物，以及用于制备和使用所述非人动物的方法和组合物，其中所述非人动物包含人源化的淋巴细胞活化基因3(Lag3)。在一些实施方案中，所述非人动物可以描述为具有对内源性Lag3基因座的遗传修饰，使得所述非人动物表达包含人部分和内源性部分(例如，非人部分)的Lag3多肽。 Non-human animals, and methods and compositions for making and using the same, are provided, wherein the non-human animals comprise a humanization of a Lymphocyte activation gene 3 (Lag3). The non-human animals may be described, in some embodiments, as having a genetic modification to an endogenous Lag3 locus so that the non-human animals express a Lag3 polypeptide that includes a human portion and an endogenous portion (e.g., a non-human portion).